Proportionality, Divisibility and Economies of Scale - Chamberlin, Edward H. (Quarterly Journal of Economics, 1948)
The problem, 229. — Plant and envelope curves: plant average cost, 230; average cost, 231; the envelope, 234. — Divisibility and economies of scale: reasons for successively lower minima, 235; the imperfect divisibility analysis, 236; the “mathematics” of divisibility, 238; divisibility and efficiency, 239; capital equipment, 243. — Proportionality and diseconomies of scale: importance of the problem, 246; the unnecessary search for a fixed factor, 247; reasons for higher plant curves, 248; no “most efficient proportion,” 249. — Constant proportions and homogeneity: the curve of constant proportions, 250; the problem of distribution, 252. — Summary: proportions and size, 255. — Appendix: the indifference curve analysis, 257.